Analysis of the Implementation of Cashless Payment System Using Quick Response Code Indonesian Standard (QRIS) at the Cafeterias of UIN Raden Intan Lampung - Ronaldi, Alvin Destian; Choiriah, Alvi; Asmalia, Ghina; Utamie, Zathu Restie (Al-Mashrof: Islamic Banking and Finance, 2023)
This research is classified as a type of qualitative descriptive research. Sources of data in this study use the types of primary data and secondary data. Data collection techniques include observations and interviews to find out information about the financing and payment models of the Cashless System which are developing and widely used in UIN Raden Intan Lampung. After getting the data through observation and interviews, the next is the method of data analysis. After getting the data, the next step is data reduction. This is done to make it easier for researchers when looking for data and make it easier to collect data so that it can be more clearly shown in the form of an overview of the data that has been reduced. The next stage is the presentation of the data and then drawing conclusions that can explain the results of the research conducted. The results of this study state that technological advances, especially on the financial transaction side, are also affected, such as Cashless payments with various channels, including E-Wallet, M-Banking, and so on. The community obtains many benefits, especially students in the UIN Raden Intan Lampung in this Cashless / Non- Cash payment system, including Cashless payment transactions in the Campus Canteen area using the QRIS Code with M-Banking BSI, BTN, and so on.